Students Entrepreneurial Program at Faculty Economics Universitas Negeri Manado (UNIMA) - Alfred F. Pongoh; Nikolas F. Wuryaningrat (Journal of International Conference Proceedings (JICP), 2018)
Student entrepreneurship program at the Universitas Negeri Manado one of them, namely in the context of forging workshop is beneficial for students to develop specialized knowledge and technical skills. The purpose of this study was to determine the role of student entrepreneurship program to the success of the workshop in the field of found the idea and generate it. The research method used was a qualitative study which is located in the Faculty of Economics UNIMA. Data collection was through interviews with key informants consisting of UNIMA Faculty of economics, The results showed that the success of the Student Entrepreneurial Program Faculty Workshop UNIMA seen this workshop graduates have been successful in helping students become new entrepreneurs as seen from some students or graduates who have attended workshops known to have small-scale entrepreneurship. Students (graduate/ undergraduate) who have completed the workshop greatly from the student entrepreneurship program and the holding of student entrepreneurship training through workshops Faculty Economics UNIMA. With the holding of this workshop is to make graduates equipped to entrepreneurship because with the provision of these skills allow them to open a business or business-related fields of knowledge gained from the training in the workshop The conclusion of the research workshop training is one method that is helping students to acquire skills that can be used to entrepreneurship. Suggestion that students need continuous training in order to increase expertise in the field of well logging techniques, electronics,machinery, and other technical expertise. Keywords: Entrepreneurial Programs, Engineering Workshop, University Students